2021
DOI: 10.1001/jamasurg.2020.5195
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Turnbull-Cutait Pull-Through Coloanal Anastomosis for Low Rectal Cancers—Reply

Abstract: The recommendation for omission of SLNB in elderly patients is based on the CALGB 9343 study 2 in which only about one-third of patients underwent axillary surgical staging. Without axillary dissection, only 3% (6 of 200) treated with lumpectomy and tamoxifen experienced axillary recurrence. 2 There was no difference in overall survival between treatments with or without radiation therapy (RT), which is the basis for another Choosing Wisely campaign recommendation-omission of RT in elderly patients with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This is consistent with systematic reviews . Of note, the anastomotic leak rate may be further lowered following a TCA by delaying the hand-sewn anastomosis beyond the 6 to 10 days used in the study by Biondo et al In fact, in his original description, Daher Cutait did not undertake the hand-sewn anastomosis component until at least several weeks after resection to allow adequate time for the delivered left colon to scar/adhere to the pelvis and anorectal musculature. Similarly, because DLI increases risk for bowel obstruction, the rate of postoperative paralytic ileus of 24% in the CAA/DLI group vs none in the TCA group was not surprising.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…This is consistent with systematic reviews . Of note, the anastomotic leak rate may be further lowered following a TCA by delaying the hand-sewn anastomosis beyond the 6 to 10 days used in the study by Biondo et al In fact, in his original description, Daher Cutait did not undertake the hand-sewn anastomosis component until at least several weeks after resection to allow adequate time for the delivered left colon to scar/adhere to the pelvis and anorectal musculature. Similarly, because DLI increases risk for bowel obstruction, the rate of postoperative paralytic ileus of 24% in the CAA/DLI group vs none in the TCA group was not surprising.…”
supporting
confidence: 64%
“…Similarly, because DLI increases risk for bowel obstruction, the rate of postoperative paralytic ileus of 24% in the CAA/DLI group vs none in the TCA group was not surprising. However, anastomotic stricture, a recognized common problem encountered following a hand-sewn coloanal anastomosis, was not discussed and is a limitation of this study . Furthermore, although short-term results suggest that TCA does not increase postoperative morbidity rates compared with a standard CAA/DLI, we disagree with the authors in calling the TCA a safe procedure given the postoperative complication rate of 35% in a relatively healthy population: 80% with an American Society of Anesthesiologists II score, none with a body mass index (calculated as weight in kilograms divided by height in meters squared) greater than 30, and none with anemia nor malnourished.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Biondo et al and the members of the TURNBULL-BCN study group have published both short-term and, more recently, 3-year data on TCA applied to sphincter-sparing rectal cancer resections with curative intent, compared to the more common approach of creating a hand-sewn coloanal anastomosis with a diverting loop ileostomy. With 2 well-balanced groups, the TURNBULL-BCN has demonstrated that oncologic results and functional results (including incontinence, low anterior resection syndrome, and overall quality of life after surgery) were similar between both groups, as were morbidity rates and rates of permanent stoma formation.…”
mentioning
confidence: 99%